Benefits of pulmonary rehabilitation in pediatric asthma. Issue 8 (7th May 2018) - Kirkby, Stephen; Rossetti, Allison; Hayes, Don; Allen, Elizabeth; Sheikh, Shahid; Kopp, Benjamin; Patel, Alpa
Abstract: Introduction: There are limited studies evaluating the role of pulmonary rehabilitation (PR) in pediatric asthma. Methods: A retrospective chart review was performed of all pediatric patients with a diagnosis of asthma enrolled in PR. Demographics, medications, and clinical records were reviewed. In addition, PFTs, 6‐min walk test (6MWT), and patient/parent symptom and quality of life surveys before and after PR were evaluated. Results: A total of 38 patients were enrolled in PR; 18 (47%) female and 20 (53%) male. Mean participant age was 11.33 ± 3.37 (range 4‐19) years. Twenty‐two (58%) were Caucasian and nine (24%) African American. Chart review was limited by incomplete data sets for many participants. Following PR, significant improvement was noted in mean 6MWT distance (1541 vs 1616 feet, P  = 0.05) and FEV1 (89.9% of predicted versus 96.4%, P  = 0.04). Survey instruments demonstrated improvement in several clinical factors, however, there was no significant change in weight following PR despite scheduled cardiovascular exercise and dietary counseling. Conclusions: Structured PR for pediatric patients with asthma can improve 6MWT distance and FEV1 as well as subjective measures of SOB and QOL, suggesting a role for PR in the chronic management of pediatric asthma. Further prospective investigation is needed to determine if PR has positive effects on other clinical parameters of asthma control and its overall impact on childhood obesity.